COMMUNITY EMPOWERMENT PROGRAM THROUGH STIMULATION OF THE GROWTH AND DEVELOPMENT OF PRE-SCHOOL CHILDREN - Wulandari, Dewi; Ixora, Ixora; Yulidaningsih, Elok (SYNTHESIS Global Health Journal, 2024)
Background. Children's social development begins to be rather complex when children reach the age of 3 years, because children have begun to enter the most basic educational realm, namely kindergarten. Children's social development is obtained from maturity and learning opportunities from various environmental responses to children. Early childhood education is one form of effort to stimulate pre-school social development. Children's development is influenced by various factors that influence each other, including: stimulation received by children since infancy, the maturity of children when receiving stimulation, the innate characteristics of children, the attitude of parents towards children or babies and interactions between parents and children. Community purpose was to increase knowledge, insight and skills regarding stimulating growth and development in parents and pre-school age children. Implementation Method. The community service method is pre and post test, counseling on stimulation of growth and development of preschool children, training (training on how to stimulate growth and development of preschool children) for parents and teachers. The number of respondents targeted in this community service activity was 30 people at Dharma Wanita Kindergarten, Ngadisuko Village, Durenan District, Trenggalek Regency. Findings. The results of community service based on observation and evaluation are an increase in the knowledge and skills of parents and kindergarten teachers regarding the stimulation of the growth and development of preschool children. Conclusion. Community service provides benefits to parents of toddlers and kindergarten teachers. Parents and kindergarten teachers have the knowledge and skills to stimulate the growth and development of preschool children.